2022
DOI: 10.1111/jpim.12626
|View full text |Cite
|
Sign up to set email alerts
|

Organizational antecedents to bootlegging and consequences for the newness of the innovation portfolio

Abstract: Literature on strategy, innovation, and portfolio management has recently shown increased interest in the concept of planned emergence. This builds on an understanding that organizations' innovation is triggered both by deliberate top-down management approaches as well as emergent bottom-up processes.However, little is known on how to effectively plan emergence. In this context, bootlegging has been mentioned as a potential approach, describing instances in which employees choose to innovate without the knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 126 publications
0
24
0
Order By: Relevance
“…The stimuli-organism-response (SOR) model indicates that the external environment shapes the individual's cognition and leads to behavior (Vieira, 2013). Consistently, previous studies have shown that various external environmental factors, such as organizational innovation management practices, including emergent innovation initiatives, and leadership, like paradoxical leadership, have significant effects on activating employees' bootlegging (Jia et al, 2021;Globocnik et al, 2022). However, human resource management practices (HRMP) are regarded as one of the core predictors of a series of employee behaviors (Chen et al, 2018;Hewagama et al, 2019), including innovative behavior (Lei et al, 2021), have been neglected in prior literature.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The stimuli-organism-response (SOR) model indicates that the external environment shapes the individual's cognition and leads to behavior (Vieira, 2013). Consistently, previous studies have shown that various external environmental factors, such as organizational innovation management practices, including emergent innovation initiatives, and leadership, like paradoxical leadership, have significant effects on activating employees' bootlegging (Jia et al, 2021;Globocnik et al, 2022). However, human resource management practices (HRMP) are regarded as one of the core predictors of a series of employee behaviors (Chen et al, 2018;Hewagama et al, 2019), including innovative behavior (Lei et al, 2021), have been neglected in prior literature.…”
mentioning
confidence: 75%
“…Specifically, employee innovation is one of the hottest research topics in academia, but most studies focus on proper innovative behavior. Bootlegging, as an informal, innovative behavior, has been proven to have a positive effect on organizational innovation performance and ability as compared to that proper innovative behavior (Criscuolo et al, 2014;Globocnik et al, 2022), but our knowledge of its antecedents is still limited. The SOR model suggests that stimulating the external environment is the key inducement for individual behavior (Joshua et al, 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 It is a technological trial and error learning process along the business career path of enterprises, 25 which is conducive to organizational renewal and innovation, as shown in its positive correlation with the novelty of innovation portfolio. 26 Most of the existing literature on bootlegging focuses on individual employees, among which individual creativity, 27 risk affinity, 28 , 29 self-efficacy 30 , 31 and achievement orientation 32 have been determined to be related to bootlegging.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…[1][2][3] A recent study has highlighted the potential for "bootlegging innovation" to emerge in management practices that support emerging innovation initiatives, enhance the novelty of innovation portfolios, and guide the practice of innovation in specific directions. 4 In practice, Wang Xiaochuan, founder of Sogou, successfully developed the Sogou Explorer despite the opposition of his boss Zhang Chaoyang; 5 Shuji Nakamura insisted on his own ideas, bypassed corporate norms and instructions of leaders and developed the LED technology in an abandoned laboratory, which won him the Nobel Prize. It has been proven that employees' bootleg innovation plays a vital role in the development and advancement of enterprises.…”
Section: Introductionmentioning
confidence: 99%